Risco cardiovascular em portadores de hipertensão arterial e diabetes mellitus em uma unidade básica de saúde do Maranhão, Brasil. - CUNHA, Laísa Cristina Camões (2022)
Introduction: The Framingham Score is a tool capable of predicting the risk of cardiovascular events happening in 10 years, thus facilitating the organization of care in health units. Objective: To determine the cardiovascular risk by applying the Framingham Score in individuals with arterial hypertension and/or followed in a Basic Health Unit of Paço do Lumiar, Maranhão. Methods: Cross-sectional study with 141 individuals. Sociodemographic, economic, clinical, nutritional and laboratory data were evaluated and the Framingham Score was applied to determine the cardiovascular risk. The quantitative variables were expressed as mean and standard deviation, and the qualitative variables, as frequencies and percentages. The normality of the numerical variables was verified by the Shapiro-Wilk test. To compare the sociodemographic, clinical, nutritional and laboratory variables by sex, Student t test or Mann-Whitney test was used when indicated. To investigate the association of demographic, clinical, nutritional and laboratory variables with cardiovascular risk, analysis of variance or Kruskal-Wallis was used and to compare proportions, chi square test. Results: The mean age was 58.5 ± 10.5 years, there was a higher prevalence of women (67.4%), alcohol 16.3%, sedentary lifestyle 83.7%. The prevalence of hypertension was 79.4%, diabetes mellitus 46.8% and both comorbidities 26.2%. Variables with difference by sex: BMI (p-value 0.002), TC (p value 0.047) and HDL-c (p-value <0.001). The prevalence of cardiovascular risk by the Framingham Score was: 27.0% low risk, 35.4% moderate and 37.6% high. In the comparison of the score by sex, 56.5% of men were classified as high cardiovascular risk, women 28.4%. In the stratification of cardiovascular risk, there were differences in scores: Age (p-value <0.001), TC (p-value 0.002), HDL-c (p-value 0.016), SBP (p value 0.001) and DM (p-value 0.041). Conclusion: The findings of this study showed that high cardiovascular risk was more prevalent in the male population and the factors of high risk were: older age, higher TC, lower HDL-c, higher SBP and presence of DM.